2014
DOI: 10.3390/rs6053693
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Estimation of Above Ground Biomass Using Dual Polarimetric PALSAR and ETM+ Data in the Hyrcanian Mountain Forest (Iran)

Abstract: Abstract:The objective of this study is to develop models based on both optical and L-band Synthetic Aperture Radar (SAR) data for above ground dry biomass (hereafter AGB) estimation in mountain forests. We chose the site of the Loveh forest, a part of the Hyrcanian forest for which previous attempts to estimate AGB have proven difficult. Uncorrected ETM+ data allow a relatively poor AGB estimation, because topography can hinder AGB estimation in mountain terrain. Therefore, we focused on the use of atmospheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 77 publications
1
37
1
Order By: Relevance
“…The NDVI information added to the SAR data in the third (c) test also improved the accuracy of SAR data alone, slightly more than that done by the SAR mean texture. This indicates a complementarity of the SAR and optical datatypes, as already shown by other researches [31,[33][34][35]53], and underlines the importance of forest cover information especially when considering simultaneously different vegetation communities, as in this study. When-in test (d)-both mean NDVI and mean HH SAR textures are added to the SAR backscattering statistics, only the first input is selected by the stepwise procedure, possibly due to the redundant cover information present in both HH and NDVI datasets.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The NDVI information added to the SAR data in the third (c) test also improved the accuracy of SAR data alone, slightly more than that done by the SAR mean texture. This indicates a complementarity of the SAR and optical datatypes, as already shown by other researches [31,[33][34][35]53], and underlines the importance of forest cover information especially when considering simultaneously different vegetation communities, as in this study. When-in test (d)-both mean NDVI and mean HH SAR textures are added to the SAR backscattering statistics, only the first input is selected by the stepwise procedure, possibly due to the redundant cover information present in both HH and NDVI datasets.…”
Section: Discussionsupporting
confidence: 49%
“…Texture features extracted from SAR data have proved useful in some studies to improve AGB estimates: using RADARSAT-2 C-band dual-polarization data in a complex subtropical forest, Sarker et al [29] found the Grey Level Co-occurrence Measure (GLCM; [30]) texture features more effective than the original bands; in [31], they found that the addition of GLCM textures improved a joined Landsat-ALOS PALSAR model for AGB estimation in Iranian forests; and Champion et al [32] found high correlation between GLCM textures extracted from airborne P-band cross polarization data and AGB in a French Guyana forests characterized by high carbon density.…”
Section: Introductionmentioning
confidence: 99%
“…They were also selected as robust descriptors in previous research [Ma et al, 2009;Schmidt et al, 2010;Liu et al, 2015]. A previous study indicated that robustness of single texture feature was unable to be maintained in single date dual polarization data with various tone-texture combination [Attarchi and Gloaguen, 2014]. This warrants that detailed investigations on textural properties are required, which may be linked to issues such as the complexity of landscape and pixel resolution used in the research.…”
Section: The Role Of Texturementioning
confidence: 99%
“…Thus, red edge indices are expected to favor biomass and wood volume estimation in semi-arid landscapes more than traditional VIs [6,26,29,30]. Besides the use of red edge indices, it has been suggested to additionally include texture attributes of satellite images [1,5,10,[30][31][32][33][34]. Image texture discriminates the spatial variability of neighboring pixels independent from image tone [35].…”
Section: Introductionmentioning
confidence: 99%